Education disrupted: Students beginning college during the COVID‐19 pandemic. Issue 199 (19th October 2022) - Kinzie, Jillian; Cole, James
Abstract: In the second year of the COVID‐19 pandemic, students entering college in fall 2021 had an unprecedented culmination to high school and transition to college. This chapter explores the experience of entering college students following these unprecedented circumstances, examining high school disruptions, including changes in the learning environment and its relationship to instructional mode preferences in college, and documenting students' sense of optimism for college, their mental and emotional health, and perceptions of academic difficulty. Results show that the educational impact of the pandemic was not uniform across student groups and will remain an important factor in these students' educational journey.